The effect of board effectiveness, government ownership, and audit recommendations on the financial resilience of state-owned enterprises in Indonesia / Daniel Lumban Tobing - Tobing, Daniel Lumban (2024)
Underperforming State-Owned Enterprises (SOEs) in Indonesia have been a persistent challenge to the government, with a significant number reporting financial losses annually. It was highlighted that 33% of state-owned enterprises do not have financial resilience. Financial resilience is of the utmost significance for businesses as it allows them to endure economic challenges, adapt to new conditions, and quickly bounce back from financial difficulties. Financial resilience is crucial for business stability and attractiveness for investments. Based on the Agency and Stakeholder Theory, this study examines the impact of corporate governance (board characteristics as represent by board number and government ownership) and audit recommendations on financial resilience among Indonesian state-owned enterprises and their subsidiaries that operate in the mining and energy sectors. The mining and energy sectors were chosen because of their vital role in the economy and environment and their uncertain and high-risk nature. SOEs play a significant role in modern economies, including in Indonesia, and may be seen as a vehicle for accelerating economic growth and providing public services and values. This vital role of SOEs makes auditing SOEs an essential task for Supreme Audit Institutions (SAIs). SAIs assist in establishing whether SOEs are operating in the public interest, ensuring that the products and services provided by SOEs are efficient and effective, and ensuring that their operation is fully transparent, accountable, and compliant with laws and regulations. It is crucial to complete this stage of SOEs audit to ensure the effective implementation of the auditor's recommendations by the auditees. Governance is of significance to both the public and private sectors. Boards of directors are responsible for the oversight of managerial information. Thus, it can improve financial reporting and performance, leading to resilience. The study examined 20 SOEs for five years, 2018 – 2022. The period was chosen to reflect before, the pandemic period, and after. Data was processed using OLS by SPSS. The findings confirm that board effectiveness and audit recommendations positively and significantly influenced financial resilience. However, the hypothesis that government ownership influences financial resilience is not supported. This is is probably due to the challenges in making swift and agile decisions due to cumbersome bureaucratic processes and political agendas prioritizing short-term political objectives over longterm financial sustainability. This interference can lead to inefficiencies, misallocation of resources, and hindered adaptability to market changes, ultimately negatively impacting financial resilience. The findings contribute to the enrichment of the growing literature on monitoring mechanisms in agency theory and the role of government as owner and stakeholder, especially in SOEs operating in emerging countries such as Indonesia. The findings also found SAI activities that resulted in audit recommendations improved SOEs in the mining and energy sectors’ financial resilience. This study could provide evidence to the regulators such as Ministry of SOEs and Ministry of Finance that performance audits done by Indonesia SAI are beneficial to improve SOEs financial resilience that could lead to organization resilience and sustainability. The regulators could also use the findings to develop the blueprint to create world-class Indonesia SOEs.